POTENSI KERUGIAN EKONOMI KARENA STUNTING PADA BALITA DI INDONESIA TAHUN 2013 - Renyoet, Brigitte Sarah; Martianto, Drajat; Sukandar, Dadang (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2016)
The research objective was to estimate the amount of economic potential losses due to stunting in toddlers in Indonesia. This is a descriptive research using secondary data in 2013 from various relevant institutes. Data was collected from Indonesia's Ministry of Health and Central Bureau of Statistics (CBS). Calculation from Konig (1995) and a correction factor of the Horton (1999). The results of the study that the average economic potential losses in 32 provinces in Indonesia was around Rp 96 billion-Rp 430 billion (0.15-0.67%) of the GRDP average of the provinces in Indonesia. Total cost for economic potential losses due to low productivity stunting in toddlers in Indonesia was around Rp 3,057 billion-Rp 13,758 billion (0.04-0.16%) of the total GDP of Indonesia.Keywords: economic potential losses, stunting, toddlers